Teacher candidates’ reflective thinking skills (RTSs) and pedagogical competence in EFL classrooms - Yunita Puspitasari; Desta Fitri Herawati; Muh. Fajar (Universitas Islam Malang, 2023)
This study aimed to investigate the association between English as a foreign language (EFL) teacher candidates’ reflective thinking skills (RTSs) and pedagogical competence. Employing a correlational study, a questionnaire conveying four dimensions of RTSs and the teacher candidates’ report of pedagogical performance in the microteaching course was used to collect the data on pedagogical competence. Using Google Forms, the questionnaire was administered to 52 EFL teacher candidates. The descriptive statistics identified that the RTSs of the EFL teacher candidates were categorized in the habitual action type. Pearson Product Moment yielded that the EFL teacher candidates’ RTSs and their pedagogical performance had a high positive statistically significant correlation, as the observed sig. value was .766. This finding confirmed that RTSs bridged the theoretical-practical divide, and was found as a predictive variable for pedagogical competence. Therefore, teacher education programs need to consider developing and implementing training activities to enhance student teachers’ RTSs, enabling them to make better pedagogical practices.